ANALISIS FAKTOR 4P+1S YANG MEMPENGARUHI KEPUASAN PENGGUNA JASA FASILITAS KESEHATAN RSIA NUR UMMI NUMBI SURABAYA - Hendra Siswanto; Hendrik Rizqiawan (Jurnal Ekonomi, Bisnis dan Social, 2024)
This study aims to find out and analyze what factors affect the satisfaction of users of health facilities RSIA Nur Ummi Numbi Surabaya. This type of research is qualitative descriptive research. This research will be carried out in June-July 2023, the number of key informants is 9 and the number of supporting informants is 10. Product research results: affect the satisfaction of health service users. Price: affects the satisfaction of health service users. Place : affects the satisfaction of health service users. Promotion: affects the satisfaction of health service users. Service: affects the satisfaction of health service users. The 4P + 1S factors that form the satisfaction of health service users can be used as a level of satisfaction as a basis for management in improving the quality of services and facilities.